Hyperoxaluria, Hypocitraturia, Hypomagnesiuria, and Lack of Intestinal Colonization by Oxalobacter formigenes in a Cervical Spinal Cord Injury Patient with Suprapubic Cystostomy, Short Bowel, and Nephrolithiasis - Subramanian Vaidyanathan; Gerd E. von Unruh; Ian D. Watson; Norbert Laube; Steve Willets; Bakul L. Soni (The Scientific World Journal)
Although urolithiasis is common in spinal cord injury patients, it is presumed that the predisposing factors for urinary stones in spinal cord injury patients are immobilization-induced hypercalciuria in the initial period after spinal injury and, in later stages, urine infection by urease-producing micro-organisms, e.g., Proteus sp., which cause struvite stones. We describe a patient who sustained C-7 complete tetraplegia in a road traffic accident in 1970, when he was 16 years old. Left ureterolithotomy was performed in 1971 followed by left nephrectomy in 1972. Probably due to adhesions, this patient developed volvulus of the intestine in 1974. As he had complete tetraplegia, he did not feel pain in the abdomen and there was a delay in the diagnosis of volvulus, which led to ischemia of a large segment of the small bowel. All but 1 ft of jejunum and 1 ft of ileum were resected leaving the large bowel intact. In 1998, suprapubic cystostomy was performed. In 2004, this patient developed calculus in the solitary right kidney. Complete stone clearance was achieved by extracorporeal shock wave lithotripsy. Stone analysis: calcium oxalate 60% and calcium phosphate 40%. Metabolic evaluation revealed hyperoxaluria, hypocitraturia, and hypomagnesiuria. Since this patient had hyperoxaluria, the stool was tested for Oxalobacter formigenes, a specific oxalate-degrading, anerobic bacterium inhabiting the gastrointestinal tracts of humans; absence of this bacterium appears to be a risk factor for development of hyperoxaluria and, subsequently, calcium oxalate kidney stone disease. DNA from the stool was extracted using the QIAamp DNA stool Mini Kit (Qiagen, Chatsworth, CA). The genomic DNA was amplified by polymerase chain reaction using specific primers for oxc gene (developed by Sidhu and associates). The stool sample tested negative for O. formigenes. The patient was prescribed potassium citrate mixture; he was advised to avoid oxalate-rich food, maintain recommended levels of calcium in his diet, and take live bio-yogurt. Two months later, 24-h urinary oxalate decreased from 0.618 to 0.411 mmol/day; 24-h urine citrate increased from 0.58 to 1.10 mmol/day. Six months later, an oxalate absorption test was performed. The patient swallowed a capsule, soluble in gastric juice, containing 50 mg (0.37 mmol) sodium [13C2]oxalate corresponding to 33.8 mg of [13C2]oxalic acid. The amount of labeled oxalate, excreted in urine, was measured by a gas chromatographic-mass spectrometric assay. Oxalate absorption, expressed as the percentage of the labeled dose recovered in the 24-h urine after dosing, was 8.3% (reference range: 2.3–17.5%). In addition to other conventional measures, oral administration of O. formigenes or lactic acid bacteria mixture to promote bacterial degradation of oxalate in the gut, and thus combat hyperoxaluria, may play a role in prevention of calcium oxalate kidney stones.